Voltage unbalance reduction in low voltage distribution networks with Rooftop PVs - Shahnia, Farhad; Ghosh, Arindam; Ledwich, G.; zare, F. (Institute of Electrical and Electronics Engineers ( IEEE ), 2010)
Voltage Unbalance (VU) is a power quality issue arising within the low voltage residential distribution networks due to the random location and rating of single-phase rooftop photovoltaic cells (PVs). In this paper, an analysis has been carried out to investigate how PV installations, their random location and power generation capacity can cause an increase in VU. Several efficient practical methods are discussed for VU reduction. Based on this analysis, it has been shown that the installation of a DSTATCOM can reduce VU. In this paper, the best possible location for DSTATCOM and its efficient control method to reduce VU will be presented. The results are verified through PSCAD/EMTDC and Monte Carlo simulations.